Direct Cost Analysis of Outpatient Arthroscopic Rotator Cuff Repair in Medicare and Non-Medicare Populations. Issue 10 (19th October 2016) - Narvy, Steven J.; Didinger, Tracey C.; Lehoang, David; Vangsness, C. Thomas; Tibone, James E.; Hatch, George F. Rick; Omid, Reza; Osorno, Felipe; Gamradt, Seth C.
Background: Providing high-quality care while also containing cost is a paramount goal in orthopaedic surgery. Increasingly, insurance providers in the United States, including government payers, are requiring financial and performance accountability for episodes of care, including a push toward bundled payments. Hypothesis: The direct cost of outpatient arthroscopic rotator cuff repair was assessed to determine whether, due to an older population, rotator cuff surgery was more costly in Medicare-insured patients than in patients covered by other insurers. We hypothesized that operative time, implant cost, and overall higher cost would be observed in Medicare patients. Study Design: Cohort study; Level of evidence, 3. Methods: Billing and operative reports from 184 outpatient arthroscopic rotator cuff repairs performed by 5 fellowship-trained arthroscopic surgeons were reviewed. Operative time, number and cost of implants, hospital reimbursement, surgeon reimbursement, and insurance type were determined from billing records and operative reports. Patients were stratified by payer (Medicare vs non-Medicare), and these variables were compared. Results: There were no statistically significant differences in the number of suture anchors used, implant cost, surgical duration, or overall cost of arthroscopic rotator cuff repair between Medicare and other insurers. Reimbursement was significantly higher for other payers when compared with Medicare, resulting in a mean per case deficit of $263.54 between billing and reimbursement for Medicare patients. Conclusion: Operating room time, implant cost, and total procedural cost was the same for Medicare patients as for patients with private payers. Further research needs to be conducted to understand the patient-specific factors that affect the cost of an episode of care for rotator cuff surgery.